Fluorenyl bridged metallocene compound and application thereof
By introducing fluorenyl bridged structure into bridge metallocene catalysts, the problem of insufficient thermal stability and copolymerization performance of the catalyst at high temperatures is solved, and the production of high-activity and high-molecular weight polyolefin materials is achieved, and the polyolefin polymers is improved The market competitiveness of materials.
Patent Information
- Application Number
- CN202411293377.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2024-12-13
AI Technical Summary
In the prior art, bridge metallocene catalysts have poor thermal stability at high temperatures and poor copolymerization performance, making it difficult to meet the production needs of high-performance polyolefin elastomers.
Using fluorenyl bridged metallocene compound as the main catalyst, by introducing fluorenyl bridged structure, the overall rigidity of the catalyst is maintained and the substituents on the bridge are controlled in one plane, reducing the steric hindrance around the metal center, and improving the ability of comonomer insertion .
The high activity and high temperature performance of the catalyst are achieved, the molecular weight and copolymerization properties of polyolefin polymers are significantly improved, and the competitiveness of polyolefin polymer materials is enhanced.
Smart Images

Figure BDA0005045242030000021 
Figure BDA0005045242030000031 
Figure BDA0005045242030000032
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of olefin polymerization catalysts, and specifically relates to a fluorenyl-bridged metallocene compound and application thereof. Background Art
[0002] Polyolefin materials have huge output, good mechanical properties, stable thermal properties, high cost performance and other advantages, and are widely used in various fields of industrial production and daily life. At present, with the rapid development of the photovoltaic industry and the demand for lightweight automobiles, the demand for polyolefin elastomers (POE for short) as a high-performance and high-value-added elastomer is increasing. However, the production of polyolefin elastomers such as POE requires a high-temperature solution polymerization process, which requires the catalyst to have excellent thermal stability and high activity at high temperatures, high molecular weight capacity and comonomer binding ability. Therefore, it is of great significance to develop homogeneous metal catalysts with improved high-temperature performance.
[0003] Patent CN1138796C discloses that the use of fluorenyl to replace the cyclopentadienyl in the bridged dicyclopentadienyl ring structure can further improve the heat resistance of the catalyst, so that the catalyst maintains a high catalytic activity and a high comonomer insertion ability at 170°C, and the molecular weight of the polymer product is high. CN105294779A and CN105916888B disclose a bridged dicyclopentadienyl catalyst with a dimethyl carbon bridge, which can be used for the copolymerization of ethylene and α-olefins, and has the advantages of high activity and good copolymerization performance, but the steric hindrance and rigidity on the bridge are small, so the thermal stability is poor. Patent WO0024793 discloses a bridged dicyclopentadienyl catalyst with a large alkyl substituent, which has significantly improved solubility in alkanes, but the two non-coplanar bridge substituents can twist freely around the bridging carbon, so that the angle and relative position between the two dicyclopentadienyl rings will change, resulting in a larger steric hindrance around the metal center, affecting the insertion of the large steric hindrance comonomer, and the molar insertion rate of octene is less than 10%
[0004] It can be seen that although various bridge-based complexes and their catalytic properties have been widely studied, the preparation of bridge-based metallocene catalysts with high activity, good high temperature resistance and excellent copolymerization ability still needs to be improved. Summary of the invention
[0005] In view of this, the object of the present invention is to provide a fluorenyl-bridged metallocene compound and its application. The fluorenyl-bridged metallocene compound is used as a main catalyst for olefin polymerization, has high activity, good high temperature resistance and good copolymerization activity.
[0006] To achieve this object, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a fluorenyl-bridged metallocene compound as shown in Formula I:
[0008]
[0009] wherein M is selected from the fourth subgroup transition metal;
[0010] R 1 Selected from halogen, amine, trimethylsilyl, substituted or unsubstituted C1-C6 alkyl, substituted or unsubstituted C2-C6 alkenyl, substituted or unsubstituted C6-C12 aromatic, anionic ligand or neutral ligand;
[0011] R 2 ~R 21 Each is independently selected from hydrogen, substituted or unsubstituted C1-C20 alkyl, substituted or unsubstituted C6-C12 aromatic, silicon, and halogen;
[0012] or
[0013] R 2 ~R 21 Any substituent in the group forms a ring with the adjacent substituent and the carbon atom where it is located.
[0014] Preferably, M is selected from titanium, zirconium or hafnium.
[0015] Preferably, the R 1 Selected from halogen, amine, trimethylsilyl, substituted or unsubstituted C1-C3 alkyl, substituted or unsubstituted C2-C4 alkenyl, substituted or unsubstituted C6-C10 aromatic group, anionic ligand or neutral ligand.
[0016] Preferably, the R 2 ~R 21 Each is independently selected from hydrogen, substituted or unsubstituted C1-C6 alkyl, substituted or unsubstituted C6-C10 aromatic group, silicon group, and halogen.
[0017] Preferably, the R 7 and R 8 , R 11 and R 12 , R 16 and R 17 , R 20 and R 21 Each independently forms a ring with the carbon atom on which it is located.
[0018] Preferably, the R 1 It is selected from halogen, substituted or unsubstituted C1-C2 alkyl, benzyl, amine, butadienyl, substituted or unsubstituted pentadienyl, trimethylsilyl, anionic ligand or neutral ligand.
[0019] Preferably, the cyclic structural formula is selected from any one of the following formulae 1 to 4:
[0020]
[0021] Preferably, the fluorenyl-bridged metallocene compound is selected from any one of the following formulas Ⅰ-1 to Ⅰ-20:
[0022]
[0023]
[0024] In a second aspect, the present invention provides a catalyst for olefin polymerization, comprising: a main catalyst and a co-catalyst;
[0025] The main catalyst is the fluorenyl-bridged metallocene compound involved in the above technical solution.
[0026] Preferably, the co-catalyst is selected from any one or more of triethylaluminum, triisobutylaluminum, tri-n-octylaluminum, diethylaluminum monochloride, ethylaluminum dichloride, methylaluminoxane, modified methylaluminoxane or a boron agent.
[0027] Preferably, the boron agent is selected from trispentafluorophenyl boron, triphenylcarbonium tetrakis(pentafluorophenyl)borate, long alkyl-modified yellow boron, [PhNHMe 2 ][B(C 6 F 5 ) 4 ]、[(C 18 H 37 ) 2 NHMe][B(C 6 F 5 ) 4 ] or [4-(C 18 H 37 ) 2 NHMe][B(C 6 F 5 ) 4 ] Any one or more of ].
[0028] Preferably, the molar ratio of aluminum in the co-catalyst to the metal in the main catalyst is (30-3000):1.
[0029] Preferably, the molar ratio of boron in the co-catalyst to the metal in the main catalyst is 0.5:1 to 5:1.
[0030] In a third aspect, the present invention provides a method for preparing an olefin polymer, comprising:
[0031] The olefin is polymerized in the presence of a solvent and the above catalyst to obtain an olefin polymer.
[0032] Preferably, the olefin is selected from any one or more of ethylene, propylene, 1-butene, 1-hexene, 1-octene, styrene, cyclopentene, cyclohexene, norbornene, 1,3-butadiene or 1,3-pentadiene.
[0033] Preferably, the solvent is selected from any one or more of n-hexane, ISOPAR E (E solution), cyclohexane, heptane or toluene.
[0034] Preferably, the polymerization reaction temperature is 80-210° C., and the polymerization reaction pressure is 0.5-9.0 MPa.
[0035] In a fourth aspect, the present invention provides a binary copolymer of ethylene and α-olefin, which is prepared according to the above-mentioned method for preparing an olefin polymer;
[0036] The α-olefin is selected from any one or more of propylene, 1-butene, 1-hexene, 1-octene or styrene.
[0037] Preferably, the molecular weight Mw of the binary copolymer is 150 to 900 kg·mol -1 The molar insertion rate of the olefin monomer is 9 to 40 mol%, the melting point is 25 to 95°C, the glass transition temperature is -40 to -95°C, and the transmittance is ≥91%.
[0038] Compared with the prior art, the present invention has the following beneficial effects:
[0039] The present invention provides an original and innovative fluorenyl-bridged metallocene compound, which can be used as a main catalyst in an olefin polymerization catalyst, has the characteristics of high activity, good high temperature resistance, and excellent copolymerization ability, and can enhance the competitiveness of my country's polyolefin polymer material technology market.
[0040] Unlike the fluorenyl group that only participates in the coordination of the metal as a cyclopentadienyl group, in the present invention, the fluorenyl bridged metallocene compound innovatively introduces a fluorenyl bridged structure on the bridge of the bridged metallocene compound to obtain a novel fluorenyl bridged metallocene compound. Among them, the introduction of the fluorenyl bridged structure can not only maintain the overall rigidity of the fluorenyl bridged metallocene compound as a main catalyst molecule and maintain high temperature resistance, but also control the two substituents on the bridge in one plane, and the steric hindrance is relatively small, and it is expected to obtain a higher co-monomer insertion ability. At the same time, the fluorenyl group has a five-membered ring structure in the middle, and the steric hindrance on both sides of the five-membered ring is farther away from the bridge group than the six-membered ring structure, so that the steric hindrance around the metal center is reduced, which is further conducive to the improvement of the co-monomer insertion ability. In addition, the present invention can conveniently regulate the spatial effect and electronic effect of the model metallocene compound by changing the type of substituents on the fluorenyl group, thereby achieving different catalytic properties and preparing polyolefin polymer materials with various structures and various properties.
[0041] The fluorenyl bridged metallocene compound provided by the present invention has the characteristics of cheap and readily available raw materials, simple synthesis route and high product yield. In olefin polymerization, a proper amount of MAO is used as a co-catalyst (100 to 1600 molar equivalents), and the fluorenyl bridged metallocene compound represented by formula I in which M is selected from zirconium and hafnium metals is used as the main catalyst, and exhibits extremely high activity, which can reach 15.0×10 4 g(PE)·g(M), the prepared polyethylene has high linearity and high molecular weight, the prepared ethylene and α-olefin copolymer has good elasticity, the molar insertion rate of olefin monomer is controllable, and has good light transmittance.
[0042] The test results show that the fluorenyl-bridged metallocene compound provided by the present invention is used as the main catalyst to catalyze the copolymerization of ethylene and 1-butene to obtain a polymer with a molecular weight of up to 36.9×10 4 g / mol, the highest molar insertion rate of 1-butene is 36.3%, and the highest transmittance is 91.6%. The molecular weight of the polymer obtained by copolymerization of ethylene and 1-octene is up to 34.6×10 4 g / mol, the highest 1-octene molar insertion rate was 19.5%, and the highest transmittance was 91.4%; the molecular weight of the polymer obtained by copolymerization of ethylene and propylene was as high as 28.9×10 4 g / mol, the highest ethylene molar insertion rate is 52.3%, and the highest transmittance is 91.4%. The molecular weight of the polymer obtained by copolymerization of propylene and hexene is up to 27.3×10 4 g / mol, and the molar insertion rate of hexene was the highest at 18.4%. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 This is the product sample diagram corresponding to the first group in Example 3;
[0044] Figure 2 This is the product sample diagram corresponding to the first group in Example 4;
[0045] Figure 3 This is the product sample diagram corresponding to the first group in Example 5. DETAILED DESCRIPTION
[0046] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0047] The present invention provides a fluorenyl-bridged metallocene compound as shown in formula I:
[0048]
[0049] Wherein, M is selected from the fourth subgroup transition metal, specifically selected from titanium (Ti), zirconium (Zr) or hafnium (Hf);
[0050] R 1 Selected from halogen, amine, trimethylsilyl, substituted or unsubstituted C1-C6 alkyl, substituted or unsubstituted C2-C6 alkenyl, substituted or unsubstituted C6-C12 aromatic, anionic ligand or neutral ligand capable of coordination with a lone electron pair;
[0051] R 2 ~R 21 Each is independently selected from hydrogen, substituted or unsubstituted C1-C20 alkyl, substituted or unsubstituted C6-C12 aromatic, silicon, and halogen;
[0052] Preferably, R 6 , R 7 , R 8 , R 9 , R 10 , R 11 , R 12 , R 13 , R 14 , R 15 , R 16 , R 17 , R 18 , R 19 , R 20 , R 21 Any combination of three or more substituents is an alkyl group having 1 to 20 carbon atoms or a silicon-containing group.
[0053] Preferably, R 7 , R8 , R 11 , R 12 , R 16 , R 17 , R 20 , R 21 It is an alkyl group having 1 to 20 carbon atoms or a silicon-containing group.
[0054] or
[0055] R 2 ~R 21 Any substituent in the group forms a ring with the adjacent substituent and the carbon atom where it is located.
[0056] In some embodiments of the present invention, the fluorenyl-bridged metallocene compound has a structure as shown in Formula I, wherein R 1 Preferably, it is selected from halogen, amine, trimethylsilyl, substituted or unsubstituted C1-C3 alkyl, substituted or unsubstituted C2-C4 alkenyl, substituted or unsubstituted C6-C10 aromatic, anionic ligand or neutral ligand;
[0057] R 2 ~R 21 Each is independently selected from hydrogen, substituted or unsubstituted C1-C6 alkyl, substituted or unsubstituted C6-C10 aromatic group, silicon group, halogen;
[0058] or
[0059] The R 7 and R 8 , R 11 and R 12 , R 16 and R 17 , R 20 and R 21 Each independently forms a ring with the carbon atom on which it is located.
[0060] In some preferred embodiments of the present invention, the fluorenyl-bridged metallocene compound has a structure as shown in Formula I, wherein R 1 Selected from halogen, substituted or unsubstituted C1-C2 alkyl, benzyl, amine, butadienyl, substituted or unsubstituted pentadienyl, trimethylsilyl, anionic ligand or neutral ligand;
[0061] R 2 ~R 21 Each is independently selected from hydrogen, substituted or unsubstituted C1-C3 alkyl;
[0062] or
[0063] The R 7 and R 8 , R11 and R 12 , R 16 and R 17 , R 20 and R 21 Each independently forms a ring with the carbon atom where it is located, and the ring-forming structural formula is selected from any one of the following formulas 1 to 4:
[0064]
[0065] In some other preferred embodiments of the present invention, the fluorenyl-bridged metallocene compound has a structure as shown in Formula I, wherein R 1 R is selected from halogen, substituted or unsubstituted C1-C2 alkyl, benzyl, amine, butadienyl, substituted or unsubstituted pentadienyl, trimethylsilyl, anionic ligand or neutral ligand; 2 ~R 21 Each independently preferably selected from hydrogen or alkyl, which may be the same or different; the R 6 ~R 21 They may or may not be hydrogen at the same time.
[0066] Or, R 7 , R 8 , R 9 , R 12 , R 16 , R 17 , R 20 , R 21 Adjacent substituents can be combined to form a ring. 7 and R 8 They may or may not be combined to form a ring; R 11 and R 12 They may or may not be combined to form a ring. 16 and R 17 They may or may not be combined to form a ring; R 20 and R 21 They may or may not be combined with each other to form a ring.
[0067] In some embodiments of the present invention, the fluorenyl-bridged metallocene compound has a structure as shown in Formula I, wherein R 2 , R 3 , R 4 , R 5 All of them are hydrogen atoms, or any one of them or a combination of two of them is not a hydrogen atom.
[0068] In the present invention, the "substituted" group in the above "substituted or unsubstituted" may be selected from alkyl groups and alkoxy groups.
[0069] In some specific embodiments of the present invention, the fluorenyl-bridged metallocene compound is selected from any one of the following formulas Ⅰ-1 to Ⅰ-10:
[0070]
[0071] Wherein, Formula I-1: R 1 =Chlorine; R 2 ~R 6 , R 9 ~R 10 , R 13~ R 21 =Hydrogen; R 7 , R 8 Connected to form cyclopentyl, R 11 , R 12 Connected to form cyclopentyl; M = Zr;
[0072] Formula I-2: R 1 = methyl; R 2 ~R 6 , R 9 ~R 10 , R 13~ R 16 , R 18 ~R 19 , R 21 =Hydrogen; R 7 , R 8 Connected to form cyclopentyl, R 11 , R 12 Connected to form cyclopentyl; R 17 , R 20 = tert-butyl; M = Zr;
[0073] Formula I-3: R 1 =benzyl; R 2 ~R 6 , R 9 ~R 10 , R 13~ R 15 , R 17 ~R 20 =Hydrogen; R 7 , R 8 Connected to form cyclopentyl, R 11 , R 12 Connected to form cyclopentyl; R 16 , R 21 , = tert-butyl; M = Zr;
[0074] Formula I-4: R 1 = methyl; R 2 ~R 6 , R 9 ~R 10 , R13~ R 15 , R 18 ~R 19 =Hydrogen; R 7 , R 8 Connected to form cyclopentyl, R 11 , R 12 Connected to form cyclopentyl; R 16 , R 17 The cyclized tetramethylcyclohexyl group; R 20 , R 21 The ring is tetramethylcyclohexyl; M = Zr;
[0075] Formula I-5: R 1 = methyl; R 2 ~R 6 , R 9 ~R 10 , R 13~ R 15 , R 18 ~R 19 =Hydrogen; R 7 , R 8 Connected to form cyclopentyl, R 11 , R 12 Connected to form cyclopentyl; R 16 , R 17 The cyclized tetramethylcyclohexyl group; R 20 , R 21 The ring is tetramethylcyclohexyl; M = Zr;
[0076] Formula I-6: R 1 = methyl; R 2 ~R 6 , R 9 ~R 10 , R 13~ R 15 , R 18 ~R 19 =Hydrogen; R 7 , R 8 Connected to form cyclopentyl, R 11 , R 12 Connected to form cyclopentyl; R 16 , R 17 The cyclized tetramethylcyclohexyl group; R 20 , R 21 The ring is tetramethylcyclohexyl; M = Zr;
[0077] Formula I-7: R 1 = methyl; R 2 ~R 6 , R 9 ~R 10 , R 13~ R 15, R 18 ~R 19 =Hydrogen; R 7 , R 8 Connected to form cyclopentyl, R 11 , R 12 Connected to form cyclopentyl; R 16 , R 17 The cyclized tetramethylcyclohexyl group; R 20 , R 21 The ring is tetramethylcyclohexyl; M = Zr;
[0078] Formula I-8: R 1 = methyl; R 2 ~R 6 , R 9 ~R 10 , R 13~ R 15 , R 18 ~R 19 =Hydrogen; R 7 , R 8 Connected to form cyclopentyl, R 11 , R 12 Connected to form cyclopentyl; R 16 , R 17 The ring is dimethylcyclohexyl; R 20 , R 21 The ring is dimethylcyclohexyl; M = Zr;
[0079] Formula I-9: R 1 = methyl; R 2 ~R 6 , R 9 ~R 10 , R 13~ R 15 , R 18 ~R 19 =Hydrogen; R 7 , R 8 Connected to form dimethylcyclopentyl, R 11 , R 12 Connected to form dimethylcyclopentyl; R 16 , R 17 Connected to form cyclopentyl; R 20 , R 21 Connected to form cyclopentyl; M = Zr;
[0080] Formula I-10: R 1 = methyl; R 2 ~R 6 , R 9 ~R 10 , R 13~ R 15 , R 18 ~R19 =Hydrogen; R 7 , R 8 Connected to form dimethylcyclopentyl, R 11 , R 12 Connected to form dimethylcyclopentyl; R 16 , R 17 Connected to form cyclopentyl; R 20 , R 21 Connected to form cyclopentyl; M = Zr.
[0081] In some other specific embodiments of the present invention, the fluorenyl-bridged metallocene compound is selected from any one of the following formulas Ⅰ-11 to Ⅰ-20:
[0082]
[0083] The present invention also provides a method for preparing the fluorenyl-bridged metallocene compound shown in the above formula I, comprising:
[0084] The compound represented by formula (II) reacts with the compound represented by formula (III) to obtain a ligand monolithium salt LLi;
[0085] In a nitrogen atmosphere, a lithium salt solution of a monolithium salt LLi treated with a certain amount of n-butyl lithium was mixed with MX 4 Reaction, and then treating with excess methyl lithium to obtain a fluorenyl-bridged metallocene compound shown in formula I;
[0086]
[0087] X is halogen, and M is titanium, zirconium or hafnium.
[0088] Among them, the compound represented by formula (II) is preferably prepared according to the following steps: in a nitrogen atmosphere, the compound represented by formula (IV) is dissolved in an ethanol solution containing 1 equivalent of sodium ethoxide, and 1.21 equivalents of the compound represented by formula (V) are added dropwise at 50°C. After the addition is completed, it is stirred at room temperature for 15 hours, filtered, and the solid is washed with 25 mL of ice ethanol. The solid is recrystallized with 75 mL of methanol to obtain an orange-red solid, and then washed once with 15 mL of ice methanol. The solid is vacuum dried to obtain the compound represented by formula (II).
[0089]
[0090] 18 mmol of the compound represented by formula (II) was weighed and dissolved in 120 mL of anhydrous ether. Under a nitrogen atmosphere at -35°C, 18 mmol of cyclopentadienyl lithium represented by formula (III) was added. The mixture was returned to room temperature and stirred for 7.5 h before the solvent was removed. The remaining solid was slurried with n-hexane (120 mL), filtered, washed with additional n-hexane (2×120 mL), and vacuum dried to obtain the ligand monolithium salt LLi.
[0091] The compound represented by formula (III) is prepared by reacting cyclopentadiene and butyl lithium.
[0092] In the present invention, the synthesis route of the fluorenyl-bridged metallocene compound shown in Formula I can be expressed as follows:
[0093]
[0094] Illustratively, according to the above synthetic route, the preparation method of the fluorenyl-bridged metallocene compound of formula I comprises the following steps:
[0095] According to the patent method (CN1684968A), under nitrogen atmosphere, 1 molar equivalent of ligand monolithium salt LLi and 1 molar equivalent of n BuLi is stirred in ether to form a slurry, which is gradually restored to room temperature and stirred for 3 hours. Under low temperature (-35°C), the above-mentioned ligand lithium salt is added to 1 equivalent zirconium chloride solution, restored to room temperature and stirred for 6 hours, the solvent is drained, and the product is extracted with dichloromethane (toluene) to remove LiCl, and the product is recrystallized with dichloromethane / n-hexane to obtain a dichloro compound. The volume ratio of dichloromethane to n-hexane is preferably 1: (10-20), and more preferably 1: (15-16).
[0096] Illustratively, the preparation method of the fluorenyl-bridged metallocene compound represented by formula I-2, I-4 to I-10 specifically comprises the following steps:
[0097] Under nitrogen, the dichloro compound obtained by the above preparation method was dissolved in toluene (50 mL), cooled to -35 ° C, and 2.1 equivalents of MeLi were slowly added dropwise, and the mixture was returned to room temperature for reaction for 12 hours, and the solvent was drained. The product was extracted from the solid with n-hexane, the insoluble matter was removed by filtration, and the filtrate was drained to obtain the target dimethyl complex.
[0098] The preparation method of the fluorenyl-bridged metallocene compound shown in formula I-3 specifically comprises the following steps:
[0099] Under nitrogen, the dichloro compound obtained by the above preparation method was dissolved in toluene (50 mL), cooled to -35 ° C, and 2.1 equivalents of benzyl magnesium bromide solution were slowly added dropwise, and the mixture was returned to room temperature for reaction for 12 hours, and the solvent was drained. The product was extracted from the solid with n-hexane, the insoluble matter was removed by filtration, and the filtrate was drained to obtain the target dibenzyl complex.
[0100] It should be noted that the point values involved in the above preparation method can also be adjusted according to actual production needs and are not limited to the point values listed above.
[0101] The good solvent used for recrystallization is selected from any one or more of dichloromethane, toluene or THF, and the poor solvent is selected from any one or more of n-hexane, ether or methyl tert-butyl ether.
[0102] In the present invention, the preparation of the fluorenyl-bridged metallocene compounds represented by formulas I-11 to I-20 can refer to the above method, which will not be described in detail here.
[0103] The present invention also provides a catalyst for olefin polymerization, comprising: a main catalyst and a co-catalyst, wherein the main catalyst is the fluorenyl-bridged metallocene compound involved in the above technical solution.
[0104] In the present invention, the cocatalyst is selected from but not limited to any one or more of a boron agent, aluminoxane, alkyl aluminum and alkyl aluminum chloride. The boron agent is selected from but not limited to trispentafluorophenyl boron, triphenylcarbonium tetrakis(pentafluorophenyl) borate, long alkyl-modified yellow boron, [PhNHMe 2 ][B(C 6 F 5 ) 4 ]、[(C 18 H 37 ) 2 NHMe][B(C 6 F 5 ) 4 ] or [4-(C 18 H 37 ) 2 NHMe][B(C 6 F 5 ) 4 ]; the aluminoxane is selected from but not limited to any one or more of methylaluminoxane, ethylaluminoxane or isobutylaluminoxane; the alkylaluminum is selected from but not limited to any one or more of trimethylaluminum, triethylaluminum, triisobutylaluminum or tri-n-hexylaluminum; the alkylaluminum chloride is selected from but not limited to any one or more of diethylaluminum monochloride or ethylaluminum dichloride. The cocatalyst is preferably isobutylaluminoxane.
[0105] In practical applications, the molar ratio of aluminum in the co-catalyst to the metal in the main catalyst is (30-3000):1, preferably (50-2000):1, and more preferably (100-1000):1. The molar ratio of boron in the co-catalyst to the metal in the main catalyst is 0.5:1-5:1, preferably 1:1-1.5:1, and more preferably 1.2:1.
[0106] The present invention also provides a method for preparing the above olefin polymer, which comprises:
[0107] The olefin is polymerized in the presence of a solvent and the above catalyst to obtain an olefin polymer.
[0108] In the present invention, the olefin is selected from any one or more of ethylene, propylene, 1-butene, 1-hexene, 1-octene, styrene, cyclopentene, cyclohexene, norbornene, 1,3-butadiene or 1,3-pentadiene. The solvent is selected from any one or more of n-hexane, ISOPARE (E solution), cyclohexane, heptane or toluene.
[0109] In the present invention, the above olefin is preferably polymerized at 80-210°C, more preferably 100-170°C, and at a pressure of 0.5-9.0 MPa, preferably 3.0-4.5 MPa. The polymerization time is generally 10-30 min, preferably 15-20 min.
[0110] The present invention also provides a binary copolymer of ethylene and α-olefin, which is prepared according to the above preparation method, that is, ethylene and α-olefin undergo polymerization reaction in the presence of a solvent and the above catalyst. The fluorenyl bridged metallocene compound provided by the present invention is used as the main catalyst active component, and after activation by a suitable co-catalyst, it can be used to catalyze the homopolymerization of ethylene or α-olefin and the copolymerization of ethylene and α-olefin. The α-olefin is selected from any one or more of propylene, 1-butene, 1-hexene, 1-octene or styrene.
[0111] Compared with the prior art, the fluorenyl bridged metallocene compound provided by the present invention has a simple structure synthesis, high catalytic activity, good temperature resistance, and can maintain a high catalytic activity under high temperature conditions. The present invention uses it as a main catalyst to catalyze the copolymerization of ethylene and 1-butene, ethylene and 1-octene, and ethylene and propylene, and can obtain a polymer product with a high molecular weight and a high comonomer insertion rate.
[0112] The molecular weight Mw of the binary copolymer is 150 to 900 kg·mol -1 The molar insertion rate of α-olefin is 9 to 40 mol%, the melting point is 25 to 95°C, and the glass transition temperature is -40 to -95°C.
[0113] The experimental results show that the molecular weight of the polymer obtained by copolymerization of ethylene and 1-butene is as high as 36.9×10 4 g / mol, the highest molar insertion rate of 1-butene is 36.3%, and the highest transmittance is 91.6%. The molecular weight of the polymer obtained by copolymerization of ethylene and 1-octene is up to 34.6×10 4 g / mol, the highest 1-octene molar insertion rate was 19.5%, and the highest transmittance was 91.4%; the molecular weight of the polymer obtained by copolymerization of ethylene and propylene was as high as 28.9×10 4 g / mol, the highest ethylene molar insertion rate is 52.3%, and the highest transmittance is 91.4%. The molecular weight of the polymer obtained by copolymerization of propylene and hexene is up to 27.3×10 4 g / mol, and the molar insertion rate of hexene was the highest at 18.4%.
[0114] In the present invention, the room temperature refers to a temperature of "15 to 30°C", preferably 25°C.
[0115] In order to further illustrate the present invention, the following examples are provided for detailed description. The experimental raw materials used in the following examples of the present invention are all common commercially available products.
[0116] Example 1 - Preparation of Ligand Monolithium Salt LLi
[0117] The present invention provides a ligand monolithium salt LLi of a fluorenyl-bridged diocene catalyst, the general structural formula of which is as follows:
[0118]
[0119] In this embodiment, the prepared ligand monolithium salt LLi is further specifically selected from the following 7 types of ligand monolithium salts LLi1-7, all of which have the above-mentioned general structure of the ligand monolithium salt LLi, and the specific substituents are as follows:
[0120] LLi1:R 2 ~R 6 , R 9 , R 10 , R 13~ R 21 =Hydrogen; R 7 , R 8 Connected to form cyclopentyl, R 11 , R 12 Connected to form a cyclopentyl group;
[0121] LLi2:R 2 ~R 6 , R 9 , R 10 , R 13~ R 16 , R18 , R 19 , R 21 =Hydrogen; R 7 , R 8 Connected to form cyclopentyl, R 11 , R 12 Connected to form cyclopentyl; R 17 , R 20 = tert-butyl;
[0122] LLi3:R 2 ~R 6 , R 9 , R 10 , R 13~ R 15 , R 17 ~R 20 =Hydrogen; R 7 , R 8 Connected to form cyclopentyl, R 11 , R 12 Connected to form cyclopentyl; R 16 , R 21 = tert-butyl;
[0123] LLi4:R 2 ~R 6 , R 9 ~R 10 , R 13~ R 15 , R 18 ~R 19 =Hydrogen; R 7 , R 8 Connected to form cyclopentyl, R 11 , R 12 Connected to form cyclopentyl; R 16 , R 17 The cyclized tetramethylcyclohexyl group; R 20 , R 21 The closed ring is tetramethylcyclohexyl;
[0124] LLi5:R 2 ~R 6 , R 9 ~R 10 , R 13~ R 15 , R 18 ~R 19 =Hydrogen; R 7 , R 8 Connected to form dimethylcyclopentyl, R 11 , R 12 Connected to form dimethylcyclopentyl; R 16 , R 17 The ring is dimethylcyclohexyl; R 20 , R21 The closed ring is dimethylcyclohexyl;
[0125] LLi6:R 2 ~R 6 , R 9 ~R 10 , R 13~ R 15 , R 18 ~R 19 =Hydrogen; R 7 , R 8 Connected to form dimethylcyclopentyl, R 11 , R 12 Connected to form dimethylcyclopentyl; R 16 , R 17 Connected to form cyclopentyl; R 20 , R 21 Connected to form a cyclopentyl group;
[0126] LLi7:R 2 ~R 6 , R 9 ~R 10 , R 13~ R 15 , R 18 ~R 19 =Hydrogen; R 7 , R 8 Connected to form dimethylcyclopentyl, R 11 , R 12 Connected to form dimethylcyclopentyl; R 16 , R 17 Connected to form dimethylcyclopentyl; R 20 , R 21 Connected to form dimethylcyclopentyl.
[0127] In this embodiment, the specific preparation process of the ligand single lithium salt LLi is as follows:
[0128] (1) Preparation of the compound represented by formula (III): 1 equivalent of substituted cyclopentadiene and 1 equivalent of n-butyl lithium are reacted in tetrahydrofuran at -35°C for 6 hours;
[0129] (2) Preparation of a fulvene compound represented by formula (II):
[0130] Weigh 0.25 mol of sodium ethoxide, add 190 mL of anhydrous ethanol at room temperature, and stir until the sodium ethoxide is completely dissolved to prepare an ethanol solution of sodium ethoxide. Add 0.25 mol of the compound represented by formula (IV) to the sodium ethoxide solution, heat the reaction system to 50°C and stir until it is completely dissolved. Under this temperature condition, add 0.3 mol of fluorene represented by formula (V) dropwise to the reaction system, return to room temperature after the addition is completed, and stir for 12 hours. Filter, wash the solid with 20 mL of cold ethanol, and then recrystallize with 80 mL of methanol to obtain an orange-red solid, wash it once with 10 mL of cold methanol, and vacuum dry the solid to obtain the fulvene represented by formula (II);
[0131]
[0132] (3) Preparation of ligand monolithium salt Lli, the synthesis route is as follows:
[0133]
[0134] The specific preparation method is as follows:
[0135] 18 mmol of the compound represented by formula (II) was weighed and dissolved in 120 mL of anhydrous ether. Under a nitrogen atmosphere at -35°C, 18 mmol of cyclopentadienyl lithium represented by formula (III) was added. The mixture was gradually restored to room temperature and stirred for 4.5 hours before the solvent was removed. The remaining solid was slurried with n-hexane (100 mL), filtered, washed with additional n-hexane (2×100 mL), and then dried under vacuum to obtain the ligand monolithium salt LLi.
[0136] Example 2
[0137] This embodiment provides a fluorenyl-bridged metallocene compound, whose specific structural formula is selected from any one of the following formulas I-1 to I-10:
[0138]
[0139] The preparation method is as follows:
[0140] (1) General preparation method of metal dichloride (Formula I-1, i.e. catalyst I-1)
[0141] Under nitrogen atmosphere, 3.9 mmol of ligand monolithium salt (LLi1) was weighed and added to 40 mL of ether to form a slurry. At -35 °C, the mixture was added dropwise. n BuLi 3.9mmol, gradually return to room temperature and stir for 3h. Then weigh 3.9mmol MCl 4 , add 20mL of ether at -35℃, and slowly add the above ligand monolithium salt solution into MCl 4The solution was returned to room temperature and stirred for 6 hours. The reaction reagents were drained, and the product was extracted with dichloromethane (toluene) to remove LiCl. The product was recrystallized with dichloromethane / n-hexane (volume ratio of 1:15) to obtain the compound shown in Formula I-1.
[0142] (2) General preparation method of metal dimethyl compounds (Formula I-2, I-4 to I-10, i.e., catalysts I-2, I-4 to I-10)
[0143] Under nitrogen, the dichlorides of the corresponding structures obtained by referring to the above preparation method (general preparation method of dichlorides) (dichlorides corresponding to formulas I-2, I-4 to I-10, respectively) were dissolved in toluene (50 mL), cooled to -35°C, 2.1 equivalents of MeLi were slowly added dropwise, the reaction was restored to room temperature for 12.5 hours, and the solvent was drained. The product was extracted from the solid with n-hexane, filtered and the filtrate was drained to obtain compounds shown in formulas I-2, I-4 to I-10.
[0144] (3) General preparation method of metal benzyl compounds (Formula I-3, i.e., catalyst I-3)
[0145] Under nitrogen, the dichloride obtained by the above preparation method (general preparation method of dichloride) (dichloride corresponding to formula I-3) was dissolved in toluene (50 mL), cooled to -35 ° C, and 2.1 equivalents of benzylmagnesium bromide solution were slowly added dropwise thereto, and the temperature was raised to room temperature for reaction for 12.5 hours, and the solvent was drained. The product was extracted from the solid with n-hexane, and the filtrate was drained after filtration to obtain the compound shown in formula I-3.
[0146] The experimental results are as follows:
[0147] Catalyst I-1, yield: 0.84 g, yield: 33.8%, elemental analysis: measured (calculated) C: 70.02
[0148] (70.01)H:4.46(4.45);
[0149] Catalyst I-2, yield: 0.79 g, yield: 34.1%, elemental analysis: measured (calculated) C: 78.85
[0150] (78.87)H:5.75(5.77);
[0151] Catalyst I-3, yield: 0.96 g, yield: 33.1%, elemental analysis: measured (calculated) C: 82.11
[0152] (82.11)H:5.66(5.67);
[0153] Catalyst I-4, yield: 0.92 g, yield: 34.8%, elemental analysis: measured (calculated) C: 68.76
[0154] (68.77)H:5.04(5.03);
[0155] Catalyst I-5, yield: 0.91 g, yield: 33.2%, elemental analysis: measured (calculated) C: 79.93
[0156] (79.94)H:8.76(8.75);
[0157] Catalyst I-6, yield: 0.92g, yield: 33.5%, elemental analysis: measured (calculated) C: 79.93
[0158] (79.94)H:7.13(7.14);
[0159] Catalyst I-7, yield: 1.02 g, yield: 32.1%, elemental analysis: measured (calculated) C: 81.10
[0160] (81.12)H:7.66(7.67);
[0161] Catalyst I-8, yield: 1.07 g, yield: 33.7%, elemental analysis: measured (calculated) C: 81.13
[0162] (81.12)H:7.68(7.67);
[0163] Catalyst I-9, yield: 0.94 g, yield: 33.1%, elemental analysis: measured (calculated) C: 80.62
[0164] (80.6)H:6.91(6.9);
[0165] Catalyst I-10, yield: 1.02 g, yield: 33.3%, elemental analysis: measured (calculated) C: 80.97
[0166] (80.96)H:7.45(7.44).
[0167] Example 3: Catalytic copolymerization of ethylene and 1-butene
[0168] The polymerization reaction was carried out in a 1200mL stainless steel autoclave. The polymerization autoclave equipped with mechanical stirring was vacuumed for 1.5h at high temperature, the system was cooled to 55°C, the required solvent (n-hexane) and the designed amount of 1-butene (for the convenience of calculation, the polymerization data 1-butene in the table was converted into the molar concentration relative to the n-hexane solvent) were added to the polymerization autoclave in turn, and the required amount of co-catalyst (the final total volume of the solution was 700mL) was added. The temperature in the autoclave was raised to the required polymerization temperature. After the temperature was constant, ethylene gas was introduced to make the polymerization pressure reach 4MPa. Under nitrogen atmosphere, the main catalyst configured from the glove box was transferred to the main catalyst feeding tank, and then the main catalyst was pressed into the reaction system using the ethylene pressure difference (4.5MPa), and the timing was started. The reaction was terminated after 15min of reaction. First, the temperature was quickly cooled to 55°C, and the reactor was opened after the pressure was released. The reaction mixture was poured into a mixed solution of 2.5M hydrochloric acid and ethanol with a volume ratio of 1:1, stirred for 25min, filtered, and the polymer product was dried in a vacuum oven. The polymer was weighed, and its molecular weight and molecular weight distribution were analyzed by high temperature GPC. The comonomer insertion rate was analyzed by high temperature quantitative carbon spectrum. The results are shown in Table 1.
[0169] Table 1 Data of ethylene and 1-butene copolymerization catalyzed by catalysts I-1 to I-10 as main catalysts a
[0170]
[0171]
[0172] a Polymerization conditions: the dosage of the main catalysts I-1 to I-10 was 1 μmol, the co-catalyst was MMAO-7, Al / M=400 (i.e., the molar ratio of the Al content in the co-catalyst to the main catalyst), the polymerization temperature was 170° C., the polymerization pressure was 4.5 MPa, and the polymerization time was 15 min; b Molecular weight and molecular weight distribution were measured by GPC; c Depend on 13 CNMR measured that d The co-catalyst is MMAO-3A, Al / M=500; e The co-catalyst is trispentafluorophenyl boron, MMAO-3A, B / M=1.5, Al / M=150; f The co-catalyst is triphenylcarbonium tetrakis(pentafluorophenyl)borate and triisobutylaluminum, B / M=1.5, Al / M=100; g The cocatalyst is [PhNHMe 2 ][B(C 6 F 5 ) 4 ], tri-n-octylaluminum, B / M=1.5, Al / M=150;h The co-catalyst is [(C18H37) 2 NHMe][B(C 6 F 5 ) 4 ], tri-n-octylaluminum, B / M=1.5, Al / M=150.
[0173] Figure 1 This is a product sample diagram corresponding to the first group (ie, Entry=1) in this embodiment. It can be seen from the diagram that the polymer comonomer is inserted uniformly and has good transparency.
[0174] Example 4: Catalytic copolymerization of ethylene and 1-octene
[0175] The polymerization reaction was carried out in a 1200mL stainless steel autoclave. The polymerization autoclave equipped with mechanical stirring was vacuumed at high temperature for 1.5h, the system was cooled to 55°C, the required 1-octene and the designed amount of n-hexane were added to the polymerization autoclave in turn, and the required amount of modified methylaluminoxane (MMAO) was added (the final total volume of the solution was 700mL), the temperature in the autoclave was raised to the required polymerization temperature, and ethylene gas was introduced after the temperature was constant to make the polymerization pressure reach 4MPa. Under nitrogen atmosphere, the main catalyst configured from the glove box was transferred to the main catalyst feed tank, and then the main catalyst was pressed into the reaction system using the ethylene pressure difference (4.5MPa), the timing was started, and the reaction was terminated after 15min of reaction. First, the temperature was quickly cooled to 55°C, the reactor was opened after the pressure was released, and the reaction mixture was poured into a mixed solution of 2.5M hydrochloric acid and ethanol with a volume ratio of 1:1, stirred for 25min, filtered, and the polymer product was dried in a vacuum oven. The polymer was weighed, and its molecular weight and molecular weight distribution were analyzed by high-temperature GPC. The comonomer insertion rate was analyzed by high-temperature quantitative carbon spectrum. The results are shown in Table 2.
[0176] Table 2 Data of ethylene and 1-octene copolymerization catalyzed by catalysts I-7 to I-10 as main catalysts a
[0177]
[0178]
[0179] a Polymerization conditions: the dosage of the main catalyst I-5 to I-10 is 1 μmol, the co-catalyst is MMAO-7, Al / M=400, the 1-octene concentration is 1.50 mol / L, the polymerization pressure is 4.5 MPa, the polymerization temperature is 170°C, and the polymerization time is 15 min; b Molecular weight and molecular weight distribution were measured by GPC; c Depend on 13 Measured by CNMR.
[0180] Figure 2 This is a product sample diagram corresponding to the first group (ie, Entry=1) in this embodiment. It can be seen from the figure that the sample has good uniformity and slightly poor transparency, which is consistent with the result of its lower insertion rate.
[0181] Example 5: Catalytic copolymerization of ethylene and propylene
[0182] The polymerization reaction was carried out in a 1200mL stainless steel autoclave. The polymerization autoclave equipped with mechanical stirring was vacuumed for 1.5h at high temperature, the system was cooled to 40°C, and the required propylene 200g and the designed amount of solvent were added to the polymerization autoclave in sequence, and the required amount of modified methylaluminoxane (MMAO) was added (the final total volume of the solution was 700mL). The temperature in the autoclave was raised to the required polymerization temperature. After the temperature was constant, ethylene gas was introduced to make the polymerization pressure reach 2.5MPa, and the balance was 15min to fully dissolve ethylene to saturation. Under nitrogen atmosphere, the main catalyst configured from the glove box was transferred to the main catalyst feeding tank, and then the main catalyst was pressed into the reaction system using the ethylene pressure difference (3MPa), and the timing was started. The reaction was terminated after 15min of reaction. The temperature was quickly cooled to 60°C, and the reactor was opened after the pressure was released. The reaction mixture was poured into a mixed solution of 2.5M hydrochloric acid and ethanol with a volume ratio of 1:1, stirred for 25min, filtered, and the polymer product was dried in a vacuum oven. The polymer was weighed, and its molecular weight and molecular weight distribution were analyzed by high-temperature GPC. The comonomer insertion rate was analyzed by high-temperature quantitative carbon spectrum. The results are shown in Table 3.
[0183] Table 3 Data of ethylene and propylene copolymerization catalyzed by catalysts I-7 to I-10 as main catalysts a
[0184]
[0185] a Polymerization conditions: the dosage of the main catalyst I-7 to I-10 is 1 μmol, the co-catalyst is MMAO-7, Al / M=400, the polymerization pressure is 3 MPa, the polymerization temperature is 85°C, and the polymerization time is 15 min; b Molecular weight and molecular weight distribution were measured by GPC; c Depend on 13 Measured by CNMR.
[0186] Figure 3 This is the product sample diagram corresponding to the first group (ie, Entry=1) in this embodiment. It can be seen from the figure that the product has good transparency and uniformity, indicating good polymerization uniformity. It also shows that the partial insertion of ethylene affects the crystallization of the polypropylene segment, resulting in improved transparency.
[0187] Example 6: Catalytic propylene / 1-hexene copolymerization
[0188] The polymerization reaction was carried out in a 1200mL stainless steel autoclave. The polymerization autoclave equipped with mechanical stirring was vacuumed at high temperature for 1.5h, the system was cooled to 45°C, 200g of propylene and 60g of 1-hexene were added to the polymerization autoclave in turn, and the required amount of modified methylaluminoxane (MMAO) was added (the final total volume of the solution was 700mL), the temperature in the autoclave was raised to the required polymerization temperature, and the polymerization pressure was maintained at 1MPa after the temperature was constant. Under nitrogen atmosphere, the main catalyst configured from the glove box was transferred to the main catalyst feed tank, and then the main catalyst was pressed into the reaction system using the nitrogen pressure difference (1.2MPa), and the timing was started. The reaction was terminated after 15min of reaction. First, the temperature was quickly cooled to 55°C, and the reactor was opened after the pressure was released, and the reaction mixture was poured into a mixed solution of 2.5M hydrochloric acid and ethanol with a volume ratio of 1:1, stirred for 40min, filtered, and the polymer product was dried in a vacuum oven. The polymer was weighed, and its molecular weight and molecular weight distribution were analyzed by high-temperature GPC. The comonomer insertion rate was analyzed by high-temperature quantitative carbon spectrum. The results are shown in Table 4.
[0189] Table 4 Data of propylene / 1-butene copolymerization catalyzed by catalysts I-7 to I-10 as main catalysts a
[0190]
[0191] aPolymerization conditions: the dosage of main catalyst I-7~I-10 is 1 μmol, the co-catalyst is MMAO-7, Al / M=400, the polymerization pressure is 1 MPa, the polymerization temperature is 85°C, and the polymerization time is 15 min; bMolecular weight and molecular weight distribution are measured by GPC; c 13 Measured by CNMR.
[0192] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A fluorenyl-bridged metallocene compound as shown in formula I: in, M is selected from the fourth subgroup transition metal; R1 is selected from halogen, amine, trimethylsilyl, substituted or unsubstituted C1-C6 alkyl, substituted or unsubstituted C2-C6 alkenyl, substituted or unsubstituted C6-C12 aromatic, anionic ligand or neutral ligand; R2~R 21 Each is independently selected from hydrogen, substituted or unsubstituted C1-C20 alkyl, substituted or unsubstituted C6-C12 aromatic, silicon, and halogen; or R2~R 21 Any substituent in the group forms a ring with the adjacent substituent and the carbon atom where it is located.
2. The fluorenyl-bridged metallocene compound according to claim 1, characterized in that: The M is selected from titanium, zirconium or hafnium; The R1 is selected from halogen, amine, trimethylsilyl, substituted or unsubstituted C1-C3 alkyl, substituted or unsubstituted C2-C4 alkenyl, substituted or unsubstituted C6-C10 aromatic, anionic ligand or neutral ligand; R2~R 21 Each is independently selected from hydrogen, substituted or unsubstituted C1-C6 alkyl, substituted or unsubstituted C6-C10 aromatic group, silicon group, halogen; or R7 and R8, R 11 and R 12 , R 16 and R 17 , R 20 and R 21 Each independently forms a ring with the carbon atom on which it is located.
3. The fluorenyl-bridged metallocene compound according to claim 2, characterized in that: The R1 is selected from halogen, substituted or unsubstituted C1-C2 alkyl, benzyl, amine, butadienyl, substituted or unsubstituted pentadienyl, trimethylsilyl, anionic ligand or neutral ligand; The cyclic structural formula is selected from any one of the following formulae 1 to 4:
4. The fluorenyl-bridged metallocene compound according to claim 3, characterized in that: The fluorenyl-bridged metallocene compound is selected from any one of the following formulas Ⅰ-1 to Ⅰ-20:
5. A catalyst for olefin polymerization, characterized in that include: Main catalyst and co-catalyst; The main catalyst is the fluorenyl-bridged metallocene compound according to any one of claims 1 to 4.
6. The catalyst for olefin polymerization according to claim 5, characterized in that The co-catalyst is selected from any one or more of triethylaluminum, triisobutylaluminum, tri-n-octylaluminum, diethylaluminum monochloride, ethylaluminum dichloride, methylaluminoxane, modified methylaluminoxane or a boron agent; The boron agent is selected from trispentafluorophenyl boron, triphenylcarbonium tetrakis(pentafluorophenyl)borate, long alkyl-modified yellow boron, [PhNHMe2][B(C6F5)4], [(C 18 H 37 )2NHMe][B(C6F5)4] or [4-(C 18 H 37 )2NHMe][B(C6F5)4]; The molar ratio of aluminum in the co-catalyst to the metal in the main catalyst is (30-3000):1; The molar ratio of boron in the co-catalyst to metal in the main catalyst is 0.5:1 to 5:
1.
7. A method for preparing an olefin polymer, characterized in that: include: An olefin is polymerized in the presence of a solvent and the catalyst according to claim 5 or 6 to obtain an olefin polymer.
8. The preparation method according to claim 7, characterized in that: The olefin is selected from any one or more of ethylene, propylene, 1-butene, 1-hexene, 1-octene, styrene, cyclopentene, cyclohexene, norbornene, 1,3-butadiene or 1,3-pentadiene; The solvent is selected from any one or more of n-hexane, ISOPAR E, cyclohexane, heptane or toluene; The polymerization reaction temperature is 80-210° C., and the polymerization reaction pressure is 0.5-9.0 MPa.
9. A binary copolymer of ethylene and α-olefin, characterized in that: Prepared according to the preparation method of claim 7 or 8; The α-olefin is selected from any one or more of propylene, 1-butene, 1-hexene, 1-octene or styrene.
10. The binary copolymer according to claim 9, characterized in that The molecular weight Mw of the binary copolymer is 150 to 900 kg·mol -1 The molar insertion rate of the olefin monomer is 9 to 40 mol%, the melting point is 25 to 95°C, the glass transition temperature is -40 to -95°C, and the transmittance is ≥91%.
